Kewajiban Nafkah Istri pada Komunitas Khuruj menurut Kompilasi Hukum Islam: Studi Kasus di Desa Cukangkawung Kecamatan Sodonghilir Kabupaten Tasikmalaya Tahun 2023 - Dadan Dadan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Wife's Supporting Obligations in the Khuruj Community According to the Compilation of Islamic Law (Case Study in Cukangkawung Village, Sodonghilir District, Tasikmalaya Regency, 2023). certain. Negligence of the khuruj group in carrying out the rights and obligations between husband and wife which are not carried out optimally. Apart from that, many people said that quite a few of the Khuruj groups neglected their families so that some became dependents on other people. This research was conducted to determine the maintenance obligations of wives in the khuruj community in Cukangkawung Village, Sodonghilir District, Tasikmalaya Regency and the maintenance obligations of wives in the khuruj community according to the Compilation of Islamic Law. This research uses a qualitative method with a phenomenological approach, namely an approach related to understanding daily life and the subjective world (life world) of humans. using interview, observation and documentation techniques. The results of this research found that in the matter of providing birth support to the family there were no problems whatsoever apart from being in accordance with Islamic law and before they performed the khuruj they had discussed the matter first. However, when it comes to their inner livelihood, of course they are not provided well, they can only communicate via electronic means, but not all of them because there are some of them who limit their use of electronic means. Apart from that, the Compilation of Islamic Law (KHI) does not explain in detail about living in the Khuruj community. The Compilation of Islamic Law (KHI) only discusses living in general, but living in the Khuruj community is included in the living for husbands who are not there.